Prevalence of and risk factors for methicillin-resistant Staphylococcus aureus colonization among human immunodeficient virus–infected outpatients in Taiwan: oral Candida colonization as a comparator. Issue 1 (1st January 2017) - Wu, Chi-Jung; Ko, Wen-Chien; Ho, Mao-Wang; Lin, Hsi-Hsun; Yang, Yun-Liang; Lin, Jiun-Nong; Huang, I-Wen; Wang, Hui-Ying; Lai, Jui-Fen; Shiau, Yih-Ru; Hsieh, Li-Yun; Chen, Hui-Ting; et al.
ABSTRACT: Human immuodeficency virus (HIV)-infected patients receiving highly active antiretroviral therapy (HAART) and community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) have increased in recent years in Taiwan. This study was undertaken to determine the prevalence of and risk factors for nasal and oral S. aureus and MRSA colonization among contemporary HIV-infected populations. Clinical variables for S. aureus and MRSA colonization among HIV-infected outpatients from three hospitals were analyzed and compared with those for oral Candida colonization. Genetic characteristics of MRSA isolates were analyzed. A total of 714 patients were screened for nasal S. aureus colonization, and a subset of 457 patients were also screened for oral S. aureus colonization. Of all patients, 79.4% were receiving HAART, and their mean CD4 count was 472 cells/mm 3 . The colonization rates in the oral cavity, nasal cavity, and at either site were 18.8%, 31.7%, and 36.8%, respectively, for S. aureus, and 3.1%, 4.4%, and 5.5%, respectively, for MRSA. These rates were all much lower than the previously reported rate of oral Candida colonization (52.4%). By multivariate analysis, a suppressed viral load (<200 copies/mL) protected against oral S. aureus, MRSA, and Candida colonization, and recent use of antibacterial agents protected against oral and nasal S. aureus colonization. Recent incarceration increased the risk of nasal MRSA colonization, while recent hospitalization, tuberculosis, older age, and intravenous drug use increased the risk of oral Candida colonization. Candida spp. did not augment S. aureus or MRSA colonization in the oral cavity. Most of the 41 MRSA isolates recovered belonged to the SCC mec IV/ pvl -negative (51.2%) and VT / pvl -positive (26.8%) ST59 local prevalent CA-MRSA clones. Distinct carriage rates demonstrated here suggested that mucosal immunity against colonization might differ in terms of microbes and sites. A decreased risk in oral carriage of MRSA and Candida might be a benefit of HAART.